1986
DOI: 10.1128/aac.29.5.955
|View full text |Cite
|
Sign up to set email alerts
|

Comparative evaluation of a new beta-lactamase inhibitor, YTR 830, combined with different beta-lactam antibiotics against bacteria harboring known beta-lactamases

Abstract: YTR 830, a new ,-lactamase inhibitor, combined with amoxicillin or carbenicillin, showed a synergistic effect similar to that observed with clavulanic acid, and generally better than that with sulbactam, against strains harboring chromosome-encoded penicillinases and broad-spectrum ,-lactamases or plasmiddetermined 13-lactamases. With ampicillin, YTR 830 showed the best synergistic activity of the inhibitors against Proteus morganii, Citrobacterfreundii, and Enterobacter cloacae and their mutants with a derepr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
56
1

Year Published

1988
1988
2003
2003

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(58 citation statements)
references
References 7 publications
1
56
1
Order By: Relevance
“…Nevertheless, since PSE-1 is still most prevalent in P. aeruginosa and is only rarely found in members of the Enterobacteriaceae, all of the studies concerning the effects of potassium clavulanate on strains possessing this enzyme specifically have been performed in P. aeruginosa. Such studies have shown that MICs or MBCs of penicillins for P. aeruginosa with PSE-1 may be reduced by potassium clavulanate; however, they usually do not fall into the clinically achievable range (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, since PSE-1 is still most prevalent in P. aeruginosa and is only rarely found in members of the Enterobacteriaceae, all of the studies concerning the effects of potassium clavulanate on strains possessing this enzyme specifically have been performed in P. aeruginosa. Such studies have shown that MICs or MBCs of penicillins for P. aeruginosa with PSE-1 may be reduced by potassium clavulanate; however, they usually do not fall into the clinically achievable range (3,6).…”
Section: Discussionmentioning
confidence: 99%
“…The com bina tion of ta zo bac tam with peni cil lins and broad spec trum cepha lo sporins has dem on strated broad an ti mi cro bial ac tiv ity (19,20).…”
Section: T He Introduction Of Third-generation Cephalo-mentioning
confidence: 99%
“…Ta zo bac tam is a re cently stud ied peni cil lanic acid sul fone that in hib its a wide va ri ety of lac ta mases (17)(18)(19)(20)(21). The com bina tion of ta zo bac tam with peni cil lins and broad spec trum cepha lo sporins has dem on strated broad an ti mi cro bial ac tiv ity (19,20).…”
Section: T He Introduction Of Third-generation Cephalo-mentioning
confidence: 99%
“…In particular, tazobactam is a better inhibitor of the chromosomal cephalosporinases of members of the family Enterobactenaceae (Enterobacter, Serratia, and Citrobacter spp.) than are sulbactam and clavulanic acid (8,10). However, this difference might not be clinically significant.…”
mentioning
confidence: 99%
“…Piperacillin is a broadspectrum penicillin which has a high level of in vitro activity against members of the family Enterobacteriaceae and Pseudomonas aeruginosa. Tazobactam is an effective inhibitor of various types of 3-lactamases, especially the penicillinase type of Staphylococcus aureus, the TEM types, and the cephalosporinase of Bacteroides fragilis (2,3,(8)(9)(10)14). In particular, tazobactam is a better inhibitor of the chromosomal cephalosporinases of members of the family Enterobactenaceae (Enterobacter, Serratia, and Citrobacter spp.)…”
mentioning
confidence: 99%